A cana-de-açúcar como uma questão sociocientífica no ensino de ciências para a justiça social - Gomes, Amanda Eloisa Ribeiro (2024)
With the increasing advancement of technology, access to news and information has become increasingly easier. However, this ease of access to the network has caused many doubts regarding the sources of the information, since disinformation content has spread with equal ease and speed. To form subjects capable of acting in these situations, we believe that education must be liberating and dialogic, in order to overcome accommodation based on a critical attitude (Freire, 2023). One of the ways to carry out this liberating education is from socio-scientific issues (SSI), that is, controversial situations that promote teaching focused on discussions of an ethical, social and political nature, seeking to raise awareness among students, based on themes close to their life realities. Furthermore, we recognize the need for science teaching that promotes discussions about social justice, which is increasingly urgent in the Brazilian social context. Therefore, in this research, we seek to analyze the potential of the sugarcane theme as a SSI for science teaching and how it can help in discussions of social justice. To this end, action research was carried out, based on a university extension activity, with science teachers from the basic education network and future teachers (degree students in physics, chemistry or biology), in which we sought to understand these potentialities from discussions and readings in groups and in a dialogical manner, in order to relate the knowledge achieved on the topic to education focused on social justice. At the end of the extension activity, a discursive textual analysis was carried out to present the results of this research. The analyzes show us that teachers understand the need to introduce methodologies that go beyond traditional science teaching, however, they still feel trapped by content materials and school performance assessment tests, in addition to understanding the need for continued training for constant improving education. We also realize that teachers not only understand the importance, but seek to encourage discussions of a political nature in their classes, seeking the comprehensive training of students, which is one of the points proposed within socio-scientific issues. Furthermore, we also noticed that teachers perceive different ways of working with sugar cane as a SSI in science teaching, as well as fostering discussions of a social, ethical and environmental nature based on the theme, in addition to discussions about other QSC that this can encourage. Finally, the teachers presented different approaches to teaching sequences that can be applied in the classroom, both for specific physics, chemistry and biology classes, and with an interdisciplinary perspective, which reflects the potential of sugar cane as a SSI for science teaching.